Optimization of Acquisition Phase and Acquisition Time Window of Coronary Artery CT Angiography with Different Heart Rates - Ziyan LIU; Wei DING; Zepeng MA; Tianle ZHANG; Yongxia ZHAO (CT Lilun yu yingyong yanjiu)
This study aimed to determine the optimal reconstruction phase and acquisition time window for coronary computed tomography angiography (CCTA) in patients with different heart rates, by exploring the effect of the optimized scanning time window on image quality and radiation dose. One thousand patients who underwent CCTA were divided into groups A and B and were divided into nine subgroups based on their heart rate at the time of CCTA. Group A individuals underwent CCTA within a single cardiac cycle, and the optimal reconstruction phase at each heart rate was identified based on image quality. The individuals in group B were examined using the optimized scanning window in group A. Some patients underwent digital subtraction angiography (DSA) and the results were used as the gold standard. The image quality, radiation dose, and diagnostic efficiency were compared between the two groups. The findings indicated that the A1~A9 subgroups' optimal reconstruction phases were: 61%~85% RR interval; 68%~84% RR interval; 70%~82% RR interval and 34%~46% RR interval; 70%~82% RR interval and 34%~46% RR interval; 70%~82% and 36%~48% RR interval; 65%~89% and 38%~50% RR interval; 68%~84% RR interval and 36%~56% RR interval; 38%~54% RR interval; and 38%~58% RR interval. There were no significant differences in the subjective score and sensitivity and specificity of CCTA in the assessment of coronary artery stenosis between the two groups. The average effective dose (ED) in Group B was 40.17% lower than that in Group A. Narrowing the acquisition time window can lower the radiation dose of CCTA inspection while maintaining image quality.